Robotic right colectomy using the Da Vinci Single‐Site® platform: case report. Issue 3 (15th March 2013) - Morelli, Luca; Guadagni, Simone; Caprili, Giovanni; Candio, Giulio Di; Boggi, Ugo; Mosca, Franco
Abstract Background While single‐port laparoscopy for abdominal surgery is technically challenging, the Da Vinci Single‐Site® robotic surgery platform may help to overcome some of the difficulties of this rapidly evolving technique. The authors of this article present a case of single‐incision, robotic right colectomy using this device. Methods A 74‐year‐old female with malignant polyp of caecum was operated on with a single‐site approach using the Da Vinci Single‐Site® robotic surgery device. Resection and anastomosis were performed extra‐corporeally after undocking the robot. Results The procedure was successfully completed in 200 min. No surgical complications occurred during the intervention and the post‐operative stay and no conversion to laparotomy or additional trocars were required. Conclusions To the best of our knowledge, this is the first case of right colectomy using the Da Vinci Single‐Site® robotic surgery platform to be reported. The procedure is feasible and safe and its main advantages are restoration of triangulation and reduced instrument clashes. Copyright © 2013 John Wiley & Sons, Ltd.